Evidence for a Potential Role of Metallothioneins in Inflammatory Bowel Diseases - Anouk Waeytens; Martine De Vos; Debby Laukens (Mediators of Inflammation)
Inflammatory bowel diseases (IBDs) are a group of chronic, relapsing, immune-mediated disorders of the intestine, including Crohn's disease and ulcerative colitis. Recent studies underscore the importance of the damaged epithelial barrier and the dysregulated innate immune system in their pathogenesis. Metallothioneins (MTs) are a family of small proteins with a high and conserved cysteine content that are rapidly upregulated in response to an inflammatory stimulus. Herein, we review the current knowledge regarding the expression and potential role of MTs in IBD. MTs exert a central position in zinc homeostasis, modulate the activation of the transcription factor nuclear factor (NF)-𝜅B, and serve as antioxidants. In addition, MTs could be involved in IBD through their antiapoptotic effects or through specific immunomodulating extracellular effects. Reports on MT expression in IBD are contradictory but clearly demonstrate a deviant MT expression supporting the idea that these aberrations in IBD require further clarification.